لفظ الكفر في السياق القرآني: دراسة في دلالة المعنى - Muhammad Mukhlis b.Muhammad Rosli
The objective of this study is to be allotted the meaning of the term الكفر( ) based on the perspective of the holy Quran. The descriptive and analytical methods is being used by collecting and analyzing the information obtained to establish the various meaning of the word based on Qur’anic contextual. The information is analyzed based on the perspective of old Arabic Criticism, who is the first group of scholars that emphasized in case of utterance and meaning. Especially from linguists and rhetoricians. This method was chosen related to its significance in interpreting the contents of the holy Quran. The problem arose and forseen from the content that can have multiple and sometimes contradictory meaning in each clause that being used. Thus, the study conducted is focusing on figurative language and extended meaning of linguistic study in the word of الكفر( ) while giving the enlightenment on the linguistic phenomena such as the verbal meaning. At the end of the study showed that the meaning of the term (الكفر ) was referring to someone who had covered his heart with something on it. However, on Qur'anic contextual there can have multiple meanings, in addition, studies also have shown that the context of a sentence is a major factor to determining the meaning of this word.